2021
DOI: 10.1111/odi.14058
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline and tocopherol (vitamin E) with/without clodronate for the management of osteoradionecrosis: A scoping review

Abstract: Background: Treatment of osteoradionecrosis (ORN) is not a straightforward task, and it is unpredictable. However, a combination of pentoxifylline; an antioxidant drug, and tocopherol (vitamin E) works as a potent antifibrotic agent and have shown recently both significant and impressive results.Aims: This scoping review aims to investigate the most prescribed regimen of pentoxifylline and tocopherol with/without clodronate for the management of ORN.Methods: Ovid MEDLINE and EMBASE databases were used to retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…PENTO protocol is low-cost, clinically feasible, safe and well tolerated by patients. 33 More comprehensive studies, controlling confounding factors such as concomitant antibiotic therapy, are necessary to establish the effectiveness of PENTO in ORN prevention. Moreover, a standardized and widely accepted protocol is still necessary in order to obtain comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…PENTO protocol is low-cost, clinically feasible, safe and well tolerated by patients. 33 More comprehensive studies, controlling confounding factors such as concomitant antibiotic therapy, are necessary to establish the effectiveness of PENTO in ORN prevention. Moreover, a standardized and widely accepted protocol is still necessary in order to obtain comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…Te main mechanism is to inhibit fbrosis induced by radiation. And in 2023, Assim Banjar reviewed the articles published between 1997 and 2020 on the treatment of ORN with Pentoxifyline and vitamin E and found that the early use of Pentoxifyline and vitamin E could signifcantly reduce the severity of ORN and reduce the degree of injury [65][66][67]. It is mainly because Pentoxifyline and vitamin E could efectively inhibit the production of free oxygen, thus reducing the damage caused by radiation to bones.…”
Section: Use Of Pentoxifylline Combined With Vitamin Ementioning
confidence: 99%
“…4 Previous published data reported on medical management of ORN reported an overall healing rate of 54.4% 5 in the largest case cohort reported to date with smaller cases series providing a much wider spectrum of successful outcomes. 6 Though clinical and radiographic resolution using PEN-TO(CLO) have been repeatedly reported in the literature, understandably histopathological analysis of the healed area remains largely unknown. The suggestion is the healed site is a complex mix of bone, mucosa, scar and fibrous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The synergistic impact of these drugs to provide an antifibrotic effect aims to stabilise and prevent progression of the disease process and encourage healing 4 . Previous published data reported on medical management of ORN reported an overall healing rate of 54.4% 5 in the largest case cohort reported to date with smaller cases series providing a much wider spectrum of successful outcomes 6 …”
Section: Introductionmentioning
confidence: 99%